Wildland fire emission factors in North America: synthesis of existing data, measurement needs and management applications - Prichard, Susan J.; O’Neill, Susan M.; Eagle, Paige; Andreu, Anne G.; Drye, Brian; Dubowy, Joel; Urbanski, Shawn; Strand, Tara M. (International journal of wildland fire, 2020)
Field and laboratory emission factors (EFs) of wildland fire emissions for 276 known air pollutants sampled across Canada and the US were compiled. An online database, the Smoke Emissions Repository Application (SERA), was created to enable analysis and summaries of existing EFs to be used in smoke management and emissions inventories. We evaluated how EFs of select pollutants (CO, CO2, CH4, NOx, total particulate matter (PM), PM2.5 and SO2) are influenced by combustion phase, burn type and fuel type. Of the 12 533 records in the database, over a third (n = 5637) are represented by 23 air pollutants, most designated as US Environmental Protection Agency criteria air pollutants, greenhouse gases, hazardous air pollutants or known air toxins. Among all pollutants in the database, including the most common pollutants PM, CO, CO2 and CH4, records are unevenly distributed with a bias towards flaming combustion, prescribed burning and laboratory measurements. Across all EFs, records are most common for south-eastern and western conifer forests and western shrubland types. Based on identified data gaps, we offer recommendations for future studies, including targeting underrepresented air pollutants, smouldering combustion phases and improved source characterisation of wildland fire emissions.